Syngnathus chihiroe, a new species of pipefish (Syngnathidae) from southern Japan - Matsunuma, Mizuki (Zootaxa, 2017)
A new species of pipefish, Syngnathus chihiroe sp. nov., (Syngnathidae), is described on the basis of a single specimen collected off Yakushima Island (East China Sea), southern Japan in a depth of 160–162 m. The new species is readily distinguished from all congeners by the combination of the following characters: dorsal-fin rays 38, pectoral-fin rays 17, trunk rings 18, tail rings 40, subdorsal rings 3.25 + 10.0 = 13.25, head length 8.7 in standard length, snout length 2.3 in head length and snout depth 3.7 in snout length. The new species is similar to Syngnathus schlegeli Kaup 1853, the only other northwestern Pacific Ocean congener, characterized by dorsal-fin rays 30–47, trunk rings 18–20 and tail rings 38–46. However, it differs from S. schlegeli in having a greater number of pectoral-fin rays (17 in the former vs. 11–15 in the latter), and a short deep snout (snout length 2.3 in head length and snout depth 3.7 in snout length vs. 1.6–2.0 and 5.6–11.3, respectively).